Migration and rural municipio in México - Ball, John M (Georgia State University, 1971)
This project, in reality, began in 1960. In that year the writer was engagec in research on the city of Tepic and made his first contact with the fact of migration in Mexico. The growth of Tepic from approsimately 25,000 in 1950 to 50,000 in 1960 could not be accounted for by natural increase alone. The numerous nwe residential developments which were then beginning to encircle the city were a testament to rapid urban growth. Unfortunately, investigating the various components of migration was not included in the objectives of that project.